2018
DOI: 10.1111/mcn.12662
|View full text |Cite
|
Sign up to set email alerts
|

Small‐scale egg production centres increase children's egg consumption in rural Zambia

Abstract: Animal source foods can efficiently enhance dietary quality, but they remain inaccessible and unaffordable for many women and young children in remote, low-income communities. We piloted an intervention in which 20 groups established egg production centres (EPCs) in their rural Zambian communities to increase the availability of eggs in the local food system. In a repeated cross-sectional design over 1 year (midline [4 months after the start of egg production] and endline [11 months]), we evaluated programme i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
(62 reference statements)
3
17
0
Order By: Relevance
“…The first paper provides an overview of the role of eggs in the diet of maternal and child nutrition and updated data on egg consumption (Lutter, Iannotti, & Stewart, ), while the second summarizes how social marketing was used in a randomized controlled trial of eggs early in the complementary feeding period to foster brand loyalty and high compliance, as well as empowerment of participants and policy change in Ecuador (Gallegos et al, ). The third and fourth papers examine how a controlled intervention to foster poultry production affected child dietary diversity and nutritional status in Ghana (Marquis et al, ) and Zambia (Dumas, Lewis, & Travis, ), while the fifth paper reviews successes and lessons learned from a project on small‐scale poultry production to increase egg production and household egg intake in four diverse African contexts (Nordhagen & Klemn, ). A novel approach to use chicken eggshells to improve dietary calcium intake in rural sub‐Saharan Africa is reported in the sixth paper (Bartter et al, ), while the seventh paper reports on business models for poultry production in East Africa and India (Beesabathuni, Lingala, & Kraemer, ).…”
mentioning
confidence: 99%
“…The first paper provides an overview of the role of eggs in the diet of maternal and child nutrition and updated data on egg consumption (Lutter, Iannotti, & Stewart, ), while the second summarizes how social marketing was used in a randomized controlled trial of eggs early in the complementary feeding period to foster brand loyalty and high compliance, as well as empowerment of participants and policy change in Ecuador (Gallegos et al, ). The third and fourth papers examine how a controlled intervention to foster poultry production affected child dietary diversity and nutritional status in Ghana (Marquis et al, ) and Zambia (Dumas, Lewis, & Travis, ), while the fifth paper reviews successes and lessons learned from a project on small‐scale poultry production to increase egg production and household egg intake in four diverse African contexts (Nordhagen & Klemn, ). A novel approach to use chicken eggshells to improve dietary calcium intake in rural sub‐Saharan Africa is reported in the sixth paper (Bartter et al, ), while the seventh paper reports on business models for poultry production in East Africa and India (Beesabathuni, Lingala, & Kraemer, ).…”
mentioning
confidence: 99%
“…Similarly, in rural Zambia, 82% of women agreed eggs were good for pregnant women and only 8% voiced concerns. 29 The main concern about eggs during pregnancy in our study was that eating too many could lead to a large baby, delivery complications, and potentially a Cesarean section. Although some participants also raised this concern about other protein-and fat-rich foods, our study did not systematically explore cultural beliefs related to eating other foods during pregnancy beyond eggs; thus, we do not know whether this concern is unique to eggs or protein-and fat-rich foods or if it applies to eating too much of any food.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, in rural Zambia, 82% of women agreed eggs were good for pregnant women and only 8% voiced concerns. 29…”
Section: Discussionmentioning
confidence: 99%
“…Margins are adequate, with a net income per farmer of USD 144 per month. A similar approach is described in two previous papers in this supplement (Beesabathuni et al, ; Dumas et al, ). For countries with large rural land areas, which, as we have seen, would require more than 200 hubs to ensure an egg for everyone, creating incentives for private companies to set up the hubs is the likely accelerated pathway to scale.…”
Section: Discussionmentioning
confidence: 95%
“…Previous papers in this supplement (Dumas, Lewis, & Travis, ; Marquis et al, ) have shown that it is possible for poor rural communities in developing countries to increase their egg production and that increased egg consumption for young children can result. While not a focus of this supplement, other authors have documented the rise of large‐scale commercial egg producers, which are expanding rapidly in countries such as Thailand, India, Saudi Arabia, and South Africa (Mehta & Nambiar, ; Narrod, Tiongco, & Costales, ; WATTAgNet, ; Windhorst, ).…”
Section: Introductionmentioning
confidence: 97%